A New Xanthone from the Fermentation Products of Endophytic Fungus of Phomopsis Species - Yang, Yuchun; Yang, Haiyin; Li, Yinke; Ye, Yanqing; Hu, Qiufen; Gao, Xuemei; Du, Gang (Asian Journal of Chemistry, 2014)
A new xanthone, 1,3-dihydroxy-4-(1,3,4-trihydroxybutan-2-yl)-8-methoxy-9H-xanthen-9-one (1) was isolated from the fermentation products of a Phomopsis fungus. Their structures were elucidated by spectroscopic methods, including extensive 1D- and 2D- NMR techniques. Compound 1 was also evaluated for their cytotoxicity against five human tumor cell lines and it showed high cytotoxicity against A549 and PC3 cell with IC50 values of 5.8 and 3.6 μM, respectively.